The Environmental Impact and the Management System of Companies - Barquero Cabrero Eserp, Jose Daniel; Medina Elizondo, Manuel (Opción, 2015)
The central idea of this article is to show some aspects related to issues of environment and sustainability. Also its purpose is to encourage the awareness that environmental protection is not a waste of money, but it is, in fact, a perspective of business that contributes to achieve the profitability of organizations. This article shows some stages of the GRECO initiative applied in the Mediterranean area, which facilitates the incorporation of SMEs to a better environmental management which would translate into an increase of profitability.Â Â